Regulated cell death. - Ashkenazi, Avi; Wells, James A. (James Allen), 1950-; Yuan, Junying (Methods in enzymology, 2014)
This volume covers research methods in apoptosis focusing on the important areas of intrinsic pathway, extrinsic pathway, caspases, cellular assays and post-apoptotic effects and model organisms; as well as topics on necroptosis and screening approaches.